Exosome-Based Delivery of Super-Repressor IκBα Alleviates Alcohol-Associated Liver Injury in Mice - Hee-Hoon Kim; Young-Ri Shim; Sung Eun Choi; Tolulope Esther Falana; Jae-Kwang Yoo; So-Hee Ahn; Minhye Park; Hyangmi Seo; Chulhee Choi; Won-Il Jeong (MDPI AG, 2023)
Activation of Kupffer cells (KCs) by gut-derived lipopolysaccharide (LPS) instigates nuclear factor-κB (NF-κB)-mediated inflammatory responses in alcohol-associated liver diseases (ALD). Here, we utilized a novel optogenetically engineered exosome technology called 'exosomes for protein loading via optically reversible protein-protein interactions (EXPLOR)' to efficiently deliver the super-repressor IκB-loaded exosomes (Exo-srIκB) to the liver and examined its therapeutic potential in acute-on-chronic alcohol-associated liver injury. We detected enhanced uptake of DiI-labeled Exo-srIκB by LPS-treated inflammatory KCs, which suppressed LPS-induced inflammatory gene expression levels. In animal experiments, a single intravenous injection of Exo-srIκB prior to alcohol binge drinking significantly attenuated alcohol-associated hepatic steatosis and infiltration of neutrophils and macrophages but not a liver injury. Notably, three consecutive days of Exo-srIκB injection remarkably reduced alcohol-associated liver injury, steatosis, apoptosis of hepatocytes, fibrosis-related gene expression levels in hepatic stellate cells, infiltration of neutrophils and macrophages, and inflammatory gene expression levels in hepatocytes and KCs. In particular, the above effects occurred with inhibition of nuclear translocation of NF-κB in liver tissues, and these beneficial effects of Exo-srIκB on ALD were shown regardless of doses. Our results suggest an exosome-based modulation of NF-κB activity in KCs by Exo-srIκB as a novel and efficient therapeutic approach in ALD.